Advances in taxation. volume 1 - Hasseldine, John (Advances in taxation, 2023)
In this 30th volume of Advances in Taxation, editor John Hasseldine includes studies from expert contributors to explore topics such as: the stock market reaction to the Tax Cuts and Jobs Act; strategic repatriations made by firms; and corporate social responsibility and tax planning. Three studies separately examine individual responses to taxation including the renunciation of U.S. citizenship due to the Foreign Account Tax Compliance Act, the imposition of a tax on sugar-sweetened beverages, and the effects of social media on tax compliance in a developing country. Reporting peer-reviewed research contributions from the U.S., Canada, and Malaysia Advances in Taxation Volume 30 is essential reading for those looking to keep abreast of the most recent research, including empirical studies using a variety of research methods from different institutional settings and contexts.